2013
DOI: 10.1159/000342222
|View full text |Cite
|
Sign up to set email alerts
|

Left Leg Apraxia after Anterior Cerebral Artery Territory Infarction: Functional Analysis Using Single-Photon Emission Computed Tomography

Abstract: Left hand apraxia is known as a unique symptom of callosal apraxia, but lower limb symptoms are rarely mentioned. We report a patient who experienced left ideomotor apraxia affecting both the upper and lower limbs after a stroke in the territory of the right anterior cerebral artery. His spontaneous gait was normal, but he was unable to move his left leg intentionally either by verbal command or by imitation. His leg symptoms gradually improved over time. We evaluated the change in cerebral blood flow in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Watson et al (1986) reported two patients with left mesial hemisphere infarctions that included the SMA who had bilateral apraxia for lower limb movements. Ito et al (2013) reported a patient who was unable to move his left leg intentionally either by verbal command or by imitation after the SMA injury. Chang and Chun (2015) reported a patient with SMA infarction who presented lower limb apraxia and even noted that this apraxia might accompany disruption of the PyT.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al (1986) reported two patients with left mesial hemisphere infarctions that included the SMA who had bilateral apraxia for lower limb movements. Ito et al (2013) reported a patient who was unable to move his left leg intentionally either by verbal command or by imitation after the SMA injury. Chang and Chun (2015) reported a patient with SMA infarction who presented lower limb apraxia and even noted that this apraxia might accompany disruption of the PyT.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are laterality-indexed data in the article presently under scrutiny (see below) there are no reference as to the handedness of the patients the authors studied and no mention of the role played by the corpus callosum in underpinning the time-resolved data provided by the authors (Hagge et al, 2016). The awareness of a newly discovered circuitry would have provided the authors the means for discovering the lateralization of the onset hemisphere in seizures seen in their patients (Derakhshan, 2008;Ito et al, 2013). 2.…”
Section: Laterality Of Motor Control As Revealed In Bicepsmentioning
confidence: 99%
“…2. Concerning the laterality indexed data buried in the article I would like to bring to the attention of the respected authors the existence of a lateralized command center based on the presence of directionality in callosal traffic (Derakhshan, 2008;Ito et al, 2013). Thus, in those who are truly right handed, the commands for moving both hands are issued in the major hemisphere located on the left side of the brain.…”
Section: Laterality Of Motor Control As Revealed In Bicepsmentioning
confidence: 99%